Enhanced recovery for obese patients undergoing gynecologic cancer surgery. Issue 10 (26th October 2020) - Harrison, Ross; Iniesta, Maria D; Pitcher, Brandelyn; Ramirez, Pedro T; Cain, Katherine; Siverand, Ashley M; Mena, Gabriel; Lasala, Javier; Meyer, Larissa A
Abstract : Objective: To compare post-operative length of stay and complication rates of matched obese and non-obese patients in an enhanced recovery (ERAS) program after open gynecologic cancer surgery. Methods: We performed an observational cohort study of patients (n=1225) undergoing open surgery from November 2014 to November 2018 at a tertiary cancer center. Patients undergoing multidisciplinary procedures, non-oncologic surgery, or procedures in addition to abdominal surgery were excluded (n=190). Obese and non-obese patients were matched by date, age, disease status, and surgical complexity. The primary outcome was post-operative length of stay. Secondary outcomes included 30-day peri-operative complications, re-operation, re-admission, opioid use, and program compliance. Results: After matching, 696 patients (348 obese, 348 non-obese) with median age of 57 years (IQR 48–66) were analyzed. Obese patients had a longer median procedure time (218 min vs 192.5 min, p<0.001) and greater median estimated blood loss (300 mL vs 200 mL, p<0.001). Median (IQR) post-operative length of stay was the same for obese and non-obese patients: 3 days (IQR 2–4). Obese and non-obese patients had similar rates of grade III–IV complications (10.9% and 6.6%, respectively, p=0.06), re-operation (2.3% and 1.4%, respectively, p=0.58), and re-admission (11.8% and 8.0%, respectively, p=0.13). Grade I–II complications were more common among obese patients (62.4% vs 48.3%, p<0.001) because they had more wound complications (17.8% vs 4.9%, p<0.001). Obese patients received more opioids both during surgery (morphine equivalent dose 57.25 mg (IQR 35–72.5) vs 50 mg (IQR 25–622.5), p=0.003) and after surgery (morphine equivalent daily dose 45 mg/day (IQR 10–96.2) vs 29.37 mg/day (IQR 7.5–70), p=0.01). Obese and non-obese patients had similar ERAS program compliance (70.1% and 69.8%, respectively, p=0.32). Conclusions: Neither post-operative length of stay nor the rate of serious complications differed significantly despite longer surgeries, greater blood loss, and more opioid use among obese patients. An ERAS program was safe, effective, and feasible for obese patients with suspected gynecologic cancer.